A Fuzzy Control MIMO for Stabilization and attitude of a Cube Sat - Mendoza Torres, Gustavo; Ródriguez Gómez, Gustavo (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In the present paper, we design the Multiple Input-Multiple Output (MIMO) fuzzy control algorithm to manipulate the Inertial Mechanical System (IMS) that stabilizes the chaotic movement and attitude the CubeSat in outer space. The inclination of the CubeSat is obtained by installing two IMS within this, installed on perpendicular faces. Each IMS consists of a reaction wheel and a motor. The torque generated by the IMS causes the angular moment that originates the inclination of the parallel axis to the CubeSat face. We will call this parallel axis a rotation axis. The inclination of each one of the rotation axes is considered a variable for each axis. Based on the Control theory, the variable is a state variable, simultaneously it is a linguistic variable of fuzzy set theory. Then we developed the Multiple Input-Multiple Output (MIMO) fuzzy control algorithm of the CubeSat’s IMS. The information that is needed to build the fuzzy sets and the bases of rules for the design of the control algorithm is obtained through simulations using the Solidworks environment.